Efektivitas Penggunaan Game Analisis Training terhadap Peningkatan Kemampuan Berpikir Induktif Remaja - Wenda Novayani; Heri Sasmita (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Inductive-reasoning is a step to draw general conclusions from individual matters. IR can be measured using the Intelligent Structure (IST) sub-ZR using a number pattern and using an Inductive Reasoning Test (IRT), which is an image pattern. One of the learning methods that are interesting and fun and student-cantered learning is Educational Game media. This study aims to see the effectiveness of games in learning to improve the students' inductive thinking skills at SMP YKPP Sungai Pakning. This study used a pre-experimental method with one group pretest-posttest conducted on 30 students of class IX B as the experimental subject. The data collection technique was implemented using a test instrument in 20 essay questions for IST and 30 objective questions for IRT. The material used in this game has also passed the validation stage carried out by a psychologist in Pekanbaru. Data were analyzed using the T-Test and score gain. Based on the study results, this game is believed to be 95% effective in improving adolescent inductive thinking skills, with an average increase of 26.6 points in the IST form and 17.8 points in the IRT form. Learning media with games are effectively applied to inductive-learning and can be used as an alternative to learning inductive-thinking at SMP YKPP Sungai Pakning.